Integrated Management of Construction and Demolition Waste as Key Factor of Urban Circular Economy - Elena, Samourkasidou; Konstantinos, Kitis; Giorgos, Gkiouzepas (Journal of Sustainability and Environmental Management, 2022)
This paper has highlighted the importance of implementing a comprehensive action plan to promote the circular economy at municipal level using as a case study of the municipality of Kavala in the management of construction and demolition waste. There is a strong interest in this particular sector due to the significant building stock that requires demolition and also the pressures to the municipal waste management services due to the small-scale renovations of mainly short-term tourist accommodation. This study was conducted to understand the impact of an integrated strategic circular economy approach to urban sustainable development and resilience. To identify this correlation, the upper strategy was analyzed in its partial components and key pillars following the four-helix model while a link with the broader theoretical framework was formulated. Of particular added value is the underlining of the barriers and weaknesses identified during the planning process, which can act as a pilot in all corresponding Greek medium-sized cities. The results suggest that the integrated management of construction and demolition waste, which comprises actions at all distinct stages (raising awareness, planning, implementation and monitoring) have a positive impact on achieving the SDGs and in creating conditions for urban resilience. However, a quantitative assessment is recommended in order to evaluate through specific indicators when this strategy moves into the implementation phase.